Mechanical and Thermal Study of Hydrate Bearing Sediments - Yun, Tae Sup (Georgia Institute of Technology, 2005)
Gas hydrate is a naturally occurring crystalline compound formed by water molecules and encapsulated gas molecules. The interest in gas hydrate reflects scientific, energy and safety concerns - climate change, future energy resources and seafloor stability. Gas hydrates form in the pore space of sediments, under high pressure and low temperature conditions. This research focuses on the fundamental understanding of hydrate bearing sediments, with emphasis on mechanical behavior, thermal properties and lens formation. Load-induced cementation and decementation effects are explored with lightly cemented loose and dense soil specimens subjected to ko-loading; the small-strain stiffness evolution inferred from shear wave velocity measurement denounces stiffness loss prior to structural collapse upon loading. Systematic triaxial tests address the intermediate and large strain response of hydrate bearing sediments for different mean particle size, applied pressure and hydrate concentration in the pore space; hydrate concentration determines elastic stiffness and undrained strength when Shyd>45%. A unique sequence of particle-level and macro-scale experiments provide new insight into the role of interparticle contact area, coordination number and pore fluid on heat transfer in particulate materials. Micro-mechanisms and necessary boundary conditions are experimentally analyzed to gain an enhanced understanding of hydrate lens formation in sediments; high specific surface soils and tensile stress fields facilitate lens formation. Finally, a new instrumented high-pressure chamber is designed, constructed and field tested. It permits measuring the mechanical and electrical properties of methane hydrate bearing sediments recovered from pressure cores without losing in situ pressure (~20MPa). Ph.D.